Plasticizer Design Principle of "Like Dissolves Like" Semiconductor Fluid Plasticized Stretchable Fully π-Conjugated Polymers Films for Uniform Large-Area and Flexible Deep-Blue Polymer Light-Emitting Diodes - Ma, Jingyao (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.